Leaving no one behind: addressing the sexuality of people with disabilities - Obasanjo Afolabi Bolarinwa; Clifford Odimegwu; Yusuff Adebayo Adebisi (BMC, 2024)
Abstract Addressing the sexuality of individuals with disabilities is important within the framework of global health and societal inclusivity. Despite comprising 16% of the world's population, this demographic faces sexual autonomy inequality. Acknowledging this intersection is pertinent for achieving inclusive healthcare and upholding the commitments of the 1994 International Conference on Population and Development and the 2006 United Nations Convention on the Rights of Persons with Disabilities. Dispelling stereotypes and promoting dialogue are key to empowering individuals with disabilities and ensuring equitable access to sexual health resources. Integrating sexual health and rights into broader healthcare systems is vital for creating an inclusive society where no one is left behind. This article advocates for the need to address the specific sexual health needs and rights of individuals with disabilities, to implement inclusive policies, and to foster a healthcare environment that respects and supports their autonomy and dignity.